Finding the Locus of Project Management Principles in School Leadership and Management: A Conceptual Perspective - Mafuwane, Barber Mbangwa (Journal of Education and Practice, 2024)
Purpose: The purpose of this study is to find the place and influence of project management principles in the leadership and management of schools. Methodology: This study adopted a qualitative research approach to collect data from project management and school leadership and management literature. The literature that was of interest for this study was mainly the literature that focused on the changes in the education system of South Africa and the impact thereof on the role of principals and the functionality of schools as organizations. Findings: This study established that principals of schools have applied project management principles and practices for ages in their craft without being conscious about it; and that their role as leaders and managers of schools has always been the same as those of project managers in big companies and industries. Unique contribution to theory, policy and practice: The study further proposed that policy makers need to intervene in the training and development of school leaders and their staff members to prepare them for a cross-functional and cross-organizational consciousness that exists in their daily activities in their schools.